An account on the history of pharmacology in Spain - Ana María Aldea-Perona; Jesús Flórez Beledo; Jesús Frías Iniesta; Antonio G. García; Juan Tamargo; Francisco Zaragozá (Elsevier, 2024)
Here we present an account on the history of pharmacology in Spain. Pharmacology as an independent science in Europe began with the creation of university chairs. Of particular relevance was the appointment in 1872 of Osswald Shmiedeberg as chairman of an Institute of Pharmacology at the University of Strassbourg, Germany. Teófilo Hernando pioneered in Spain the new emerging pharmacology at the beginning of the XX Century. He made a posdoctoral stay in the laboratory of Schmiedeberg, working on digitalis. In 1912 he won the chair of "Materia Médica y Arte de Recetar" at "Universidad Central of Madrid" (today, "Universidad Complutense de Madrid", UCM). He soon decided to transform such subject to the emerging modern pharmacology, with the teaching of experimental pharmacology in the third course of medical studies and clinical therapeutics (today clinical pharmacology) in the sixth course. This was the status of pharmacology in 1920, supporting the view that Hernando was a pioneer of clinical pharmacology. However, the Spanish Civil War and the II Word War interropted this division of preclinical and clinical pharmacology; only in the 1980's was clinical pharmacolgy partially developed in Spain. From a scientific point of view, Hernando directly trained various young pharmacologists that extended the new science to various Spanish universities. Some of his direct disciples were Benigno Lorenzo Velázquez, Francisco García Valdecasas, Rafael Méndez, Tomás Alday, Gabriel Sánchez de la Cuesta, Dámaso Gutiérrez or Ramón P é rez-Cirera. One of the central research subject was the analysis of the effects of digitalis on the cat and frog heart. In the initiation of the 1970 s pharmacologists trained by those Hernando's students grew throughout various universities and the "Consejo Superior de Investigaciones Científicas" (CSIC). And hence, in 1972 the "Sociedad Española de Farmacología" (SEF) emerged. Later on, in the 1990's the "Sociedad Española de Farmacología Clínica (SEFC) also emerged. The relationship between the two societies is still weak. Out of the vast scope of the pharmacological sciences, Spanish pharmacologists have made relevant contributions in two areas namely, neuropsychopharmacology and cardiovacular pharmacology. Nonetheless, in other areas such as smooth muscle, gastroenterology, pharmacogenetics and hepatic toxicity, Spanish pharmacologists have also made relevant contributions. A succint description of such contributions is made. Finally, some hints on perspectives for the further development of preclinical and clinical pharmacology in Spain, are offered.